PENILAIAN KINERJA BERDASARKAN KOMPETENSI DAN KPI (KEY PERFORMER INDICATOR) PERUSAHAAN DAERAH AIR MINUM KABUPATEN SEMARANG - Mayasari, Isti; Haryanti, Kristiana; Hindiarto, Ferdinandus (PREDIKSI, 2012)
This research aim is about Performance Appraisal at PDAM (Perusahaan Daerah Air Minum) Kabupaten Semarang. Before this research, employees was not satisfied with performance appraisal that already in use on their company because it is doubtable not objectives, there is no feedback and it cannot use for employees improvement. Performance Appraisal Based on Competencies and KPI (Key Performance Indicator) is designed to increase objectivity of performance appraisal and to maximizing the purpose of performance appraisal itself. Performance Appraisal Based on Competencies and KPI (Key Performance Indicator) is simulated to Branch Manager level and Head of Customer Care Division. This research is qualitative research by objective interview and focus group discussion to collect the datas. The result is shows that reliability, relevance, sensitivity and practicality aspect of performance appraisal based on competencies and KPI is better than performance appraisal that already in use in this company